INTERACTION OF KAZAKHSTAN WITH THE CODEX ALIMENTARIUS COMMISSION IN THE FIELD OF IMPLEMENTATION OF STANDARDS OF THE MAIN TYPES OF FOOD PRODUCTS (Journal of actual problems of jurisprudence, 2023)
This article is devoted to the study of the general state of cooperation between Kazakhstan and the Codex Alimentarius Commission, the experience of implementing international Codex Alimentarius standards in regional and national legislation. Codex Alimentarius, being an act of "soft law", allows the introduction of international standards taking into account national legislation, the current economic situation, the level of development of the agro-industrial complex, the innovativeness of the technologies used, both in the production of agricultural products and in the process of its processing, storage, transportation and sale.Ensuring the quality of food from the "field to the counter" is the main task of the HACCP system.Keywords: Codex Alimentarius, international standards, food safety, HACCP system.